Recommendations and regulations for sport events in the heat: ReFORM summary of the International Olympic Committee`s consensus statement - Dupont, A. C.; Tooth, C.; Brocherie, F.; Racinais, S.; Bouten, J. (British Journal of Sports Medicine, 2025)
One of the main missions of ReFORM, the French-speaking Olympic sports medicine research network, is to provide a synthesis and translation of the International Olympic Committee (IOC) consensus statements in order to make them accessible and understandable to the French-speaking stakeholders surrounding athletes (coaches, scientific and medical staff).1 The IOC consensus statement on the protection of athletes competing in the heat2 provides recommendations for local organising committees, athletes, medical services and management, and policy development for international federations. This editorial presents a summary and an infographic (figure 1) of the IOC consensus recommendations and regulations for sport events in the heat.2